A Photometric and Spectroscopic Study of IC 2473, an Outer Pseudo-ring Galaxy (R′1) - Hussein, Zeinab F.; Ahmed, Abdullah K. (Iraqi Journal of Science, 2026)
This work aims to study the outer Pseudo-ring galaxy IC 2473 by analyzing its spectroscopic and photometric data using griz filters from the Sloan Digital Sky Survey (SDSS). The ellipse task from the STSDAS library was applied within the IRAF environment to analyze the isophotes and extract the galaxy’s structural and optical properties using surface photometric techniques. This analysis helped determine important parameters such as ellipticity, surface brightness, and position angle, enabling a precise characterization of the galaxy’s structure. A least-square fitting method was used to effectively study the morphological features. Spectroscopically, the emission line flux [OII] was analyzed to estimate the star formation rate (SFR), which was found to be approximately 0.124 M⊙ yr-1. The mass of the supermassive black hole (MBH) was calculated using the M–σ relationship, and it was approximately 2.2×10⁷ M⊙, with a Schwarzschild radius of 6.5×10⁷ km. In addition, the effective density of the black hole (ρ_BH) within the Schwarzschild radius was calculated and found to be approximately 3.75×10⁴ kg/m³. This study provides a comprehensive and integrated analysis of the structural, physical, and dynamical aspects of IC 2473, contributing to our understanding of the internal structure of pseudo-ring galaxies and their associated stellar activity.